Union of South Africa . House of Assembly Debates - South Africa Parliament (Cape Town, 1941)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times. Debates of the House of Assembly / Union of South Africa = Debatten van de Volksraad / Unie van Zuid-Afrika.
108 v. South Africa Politics and government
Keywords: Fifth Session; Eight Parliament; 17 March 1941; 21 March 1941; Index to Subjects; Additional estimates (motion - Mr Hofmeyr); Index to Speeches; Erasmus, Mr F.C (Moorreesburg); Wolfaard, Mr G van Z (Worcester); JC044702